2007
DOI: 10.1073/pnas.0703601104
|View full text |Cite
|
Sign up to set email alerts
|

Mother–offspring competition promotes colonization success

Abstract: Colonization is the crucial process underlying range expansions, biological invasions, and metapopulation dynamics. Which individuals leave their natal population to colonize empty habitats is a crucial question and is presently unresolved. Dispersal is the first step in colonization. However, not all dispersing individuals are necessarily good colonizers. Indeed, in some species, the phenotype of dispersers differs depending on the selective pressures that induce dispersal. In particular, kin-based interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 57 publications
2
68
1
Order By: Relevance
“…Heritability studies of brain function are uncommon. One study showed no genetic influences on brain activation in response to sad stimuli (Cote et al, 2007) whereas 43% heritability for default-mode network in the posterior cingulate region (Glahn et al, 2010) and 40-65% heritability for task-related brain activations (Blokland et al, 2011) have been observed.…”
Section: Implications Of the Findingsmentioning
confidence: 95%
“…Heritability studies of brain function are uncommon. One study showed no genetic influences on brain activation in response to sad stimuli (Cote et al, 2007) whereas 43% heritability for default-mode network in the posterior cingulate region (Glahn et al, 2010) and 40-65% heritability for task-related brain activations (Blokland et al, 2011) have been observed.…”
Section: Implications Of the Findingsmentioning
confidence: 95%
“…We decided thus to walk here on the empiricist side and to complement this theoretical exercise by selected examples drawn from real organisms. In experimental conditions, common lizards exposed to kin competition dispersed in more risky conditions than those being confronted to the competition with non kin individuals [29,30]. In the two spotted mite, relatedness, but not density, changes the shape of the dispersal kernel towards a more skewed and leptokurtic shape including a longer dispersal distance when kin competition occurs [31].…”
Section: Dispersal Evolutionary Ecologymentioning
confidence: 99%
“…For example, empiricists have shown great interest in testing whether and why dispersal could be sex-biased [31,166,167], condition-dependent (depending on food level [168], on the local density of conspecifics [155], on brood size [169], on parasite load [156] or on temperature [170]) or in testing whether habitat persistence [153], kin competition [155,171,172] or habitat fragmentation [154,173] actually affect the evolution of dispersal. Other related issues with potential immediate applications, e.g.…”
Section: Empirical Considerationsmentioning
confidence: 99%